Pyrolytic Depolymerization Mechanisms for Post-Consumer Plastic Wastes - Kirtika Kohli; Sriraam R. Chandrasekaran; Ravindra Prajapati; Bidhya Kunwar; Sultan Al-Salem; Bryan R. Moser; Brajendra K. Sharma (Energies, 2022)
Fast pyrolysis of five post-consumer plastic waste materials was studied using pyrolysis coupled with gas chromatography/mass spectrometry (Py-GC/MS) technique. Prescription medicine bottles, landfill liners, and one type of industrial plastic waste represented polyolefin-based polymers, whereas packaging material represented polystyrene, and other industrial plastic waste represented polyurethane. The noncatalytic and catalytic degradation mechanisms of all five post-consumer plastic wastes were elucidated. The noncatalytic pyrolysis experiments were conducted at a temperature of 600 °C for a residence time of 5 min. For catalytic pyrolysis, a spent FCC catalyst was utilized for polystyrene, a sulfated zirconia-based catalyst was utilized for polyurethane, and a Y-zeolite catalyst was used for polyolefinic plastic waste. The results suggested that the thermal reaction has higher monomeric and oligomeric selectivity than the catalytic reaction. Results from the catalytic runs showed that the addition of catalysts greatly influences product compositions and has a significant effect on the selectivity of a specific compound. One of the plastic wastes, landfill liner, was selected for a batch scale pyrolysis at 420–440 °C using Y-zeolite as a catalyst to demonstrate the product properties and potential use of the liquid product formed. The complete product distribution of plastic crude oil was performed followed by distillation to produce aviation range fuel. The fuel properties of aviation range fuel were examined, and results suggested that the fuel fraction can be easily blended with commercially available fuels for direct applications.